Pengaruh Ekstrak Umbi Gadung (Discorea hispida Dennst) Tarhadap Hama Daun Sawi - Sitti Nuur Jannah; Muhammad Indar Pramudi; Yusriadi Marsuni (JURNAL PROTEKSI TANAMAN TROPIKA, 2022)
Pests that often attack mustard plants are armyworm (Spodoptera litura F.), tritip caterpillar (Plutella xylostella L.), leaf caterpillar (Crocidolomia binotalis Z.), a common pest that also often attacks mustard plants is the cabbage caterpillar (Hellula undalis F. ), green steamed grasshopper (Atractomorpha crenulata), and snail (Helix pomatia). One of the efforts in controlling Plant Pest Organisms (OPT), this study aims to determine the effect of gadung tuber extract (Discorea hispida Dennst) in controlling the level of damage caused by mustard leaf pests. This vegetable pesticide comes from plants that contain toxins but the residue left does not interfere with the surrounding environment. The treatment of gadung tuber extract given in this study were water control, chemical control and four treatments of botanical pesticide concentration. This research lasted for 35 days from seeding to harvest. The results showed that each treatment had a different attack intensity level. The treatment of gadung tuber extract has the effect of being used as a botanical pesticide against mustard leaf pests because the K4 treatment (10 ml) with an attack intensity percentage of 7.97 showed the best results in controlling the level of damage to mustard leaf pests.